Constraining the physics of carbon crystallization through pulsations of a massive DAV BPM37093. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Nitta, Atsuko; Kepler, S. O.; Chené, André-Nicolas; Koester, D.; Provencal, J. L.; Kleinmani, S. J.; Sullivan, D. J.; Chote, Paul; Sefako, Ramotholo; Kanaan, Antonio; Romero, Alejandra; Corti, Mariela; et al.
Abstract: We are trying to reduce the largest uncertainties in using white dwarf stars as Galactic chronometers by understanding the details of carbon crystalliazation that currently result in a 1–2 Gyr uncertainty in the ages of the oldest white dwarf stars. We expect the coolest white dwarf stars to have crystallized interiors, but theory also predicts hotter white dwarf stars, if they are massive enough, will also have some core crystallization. BPM 37093 is the first discovered of only a handful of known massive white dwarf stars that are also pulsating DAV, or ZZ Ceti, variables. Our approach is to use the pulsations to constrain the core composition and amount of crystallization. Here we report our analysis of 4 hours of continuous time series spectroscopy of BPM 37093 with Gemini South combined with simultaneous time-series photometry from Mt. John (New Zealand), SAAO, PROMPT, and Complejo Astronomico El Leoncito (CASLEO, Argentina).